Floral diversity increases butterfly diversity in a multitrophic metacommunity. Issue 8 (9th June 2022) - Gordon, Susan C. C.; Kerr, Jeremy T.
Abstract: The impact of multitrophic interactions on metacommunity structure, despite extensive theory and modeling/manipulative studies, has remained largely unexplored within naturally occurring metacommunities. We investigated the impacts of mutualistic partners and predators on a butterfly metacommunity, as well as the impacts that local and landscape characteristics have across three trophic levels: flowering plants, butterflies, and butterfly predators. Using data for butterfly diversity/richness, flowering plant diversity/richness, and butterfly predation (on clay butterfly models) across 15 grassland sites, we posed 3 questions. (1) How do mutualist metacommunity structure, predation pressure, and local and regional habitat characteristics affect butterfly metacommunity structure? (2) How do local and regional habitat characteristics affect flowering plant metacommunity structure? (3) How do local and regional habitat characteristics affect predation pressure? Floral diversity and richness had a positive effect on butterfly diversity and richness (Question 1). Site size positively affected floral diversity and richness (Question 2), and through this relationship site size had an indirect positive effect on butterfly diversity and richness (Question 1). In contrast to previous work, no other variables impacted butterfly diversity/richness. This result was particularly surprising for predation pressure: Our results suggest that within our study system, butterfly community diversity and richness are not strongly impacted by predation. Predator attacks occurred more in larger and more isolated sites (Question 3), suggesting that predators respond more strongly to landscape characteristics than abundance or diversity of butterfly prey species. This decoupling of predation pressure and butterfly communities suggests that conserving and restoring healthy predator populations may not negatively impact butterfly communities. If diverse plant communities are maintained, even small and isolated habitat patches can be valuable for butterfly conservation, which may influence reserve design and habitat restoration strategies.